Beam Scanning Properties of a Ferrite Loaded Microstrip Patch Antenna - Sheikh Sharif Iqbal Mitu; Farooq Sultan (International Journal of Antennas and Propagation)
Axially magnetized ferrite loaded microstrip patch antenna (MPA) with tunable beam scanning properties is presented. Ferrite cylinders are optimally positioned within the near field region of the patch to introduce Ey phase tapers needed for beam scanning. The interaction between the radiated EM wave and the gyrotropic properties of ferrites is controlled by varying the magnetizing fields. A beam scan of ±30° is achieved for a DC biasing range of 0–0.19 T. Simulated antenna properties are verified using experimental results. Recent LTCC technology allows the biasing coils to be embedded within the ferrite material to considerably reduce the required external magnetizing field.